The Influence of Headmasters’ Perception About Their Position on the Performance of the State Junior High School Headmaster in Medan - Mesiono, Abur Hamdi Usman and Maimun Aqsha Lubis (International Journal of Advanced Science and Technology, 2020)
The aim of this study is to find out the headmaster perception about their position on the performance of the state junior high school in Medan. The hypothesis is there is an effect of the headmasters’ perception about their position on the performance of the State Junior High School in Medan. This study was done in state junior high school in Medan in 2018. The method is a correlational quantitative method with Path Analysis using expose facto design that is testing what has happened. The population is all of the headmasters in state junior high school in Medan that is consisted 38 headmasters. Sampling was done by using Saturation Sampling technique (Census). Based on saturation/ census sampling technique, the population of 38 junior high school headmasters in Medan City, all of whom are research samples. Instrument used to collect headmaster head's perception data about position, and headmaster performance by using questionnaire. To determine the validity of the instrument is tested through content validity and construct validity which then tested to 30 respondents outside the research sample. Data is processed and analyzed by using descriptive analysis and path analysis (phat analysis). Interpretation of result of data analysis of research done with level of significance equal to 0,05. The results showed that (1) the headmaster's perception coefficient on the position of Headmaster of Junior High School in Medan City was 0.146 with t count = 7,14 and t table = 1.69 at α = 0.05. show t count> t table then Headmaster's perception about the positions have a direct effect on the headmaster's performance. This means the better the headmasters’ perception of the position the better the headmasters’ performance.